Advanced electromagnetism: shaping the information waves of the future - Zulkifli Husain (Nanyang Technological University, 2022)
Electromagnetic waveshaping is becoming increasingly relevant to the modern, data-driven world, from the control of waves emitted from cell phone towers to the manipulation of radiation from LiDAR in autonomous vehicles. With rapid advances in shaping electromagnetic waves at every frequency, a wealth of novel waveforms has become possible, limited only by our imagination (and Maxwell’s equations). In this project, I will theoretically and numerically study novel wave-shaping schemes and their potential to realize unprecedented electromagnetic phenomena. This project will enable me to gain an understanding on how to create an algorithm that can back-calculate the needed source elements for a desired electromagnetic waveform.